La modélisation d'accompagnement Une démarche participative en appui au développement durable - Étienne, Michel (éditions Quae, 2010)
"Sustainable development and its expression in terms of participation by local stakeholders in future choices in regions where they live or work have become topical issues. Companion modelling is particularly original among methods to set up participative approaches around the sustainable management of natural renewable resources. The aim of this book is to familiarise the reader with the companion modelling approach, by presenting the scientific posture that is its foundation, its methods and tools and the special place for models. It also explains how to incorporate several decision scales, take power games into account and lastly assess the effects on the people involved in using this approach. This work is based on concrete examples taken from 27 cases studied by the researcher group and on educational tools. It is intended for researchers into rural development and renewable resources as well as students and teachers."